2018
DOI: 10.1007/s11883-018-0737-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in the Fight Against Atherosclerosis: Is This a Dead End?

Abstract: Purpose of ReviewThe purpose of this review is to focus on the outcome of recent antioxidant interventions using synthetic and naturally occurring molecules established as adjuvant strategies to lipid-lowering or anti-inflammatory therapies designed to reduce the risk of cardiovascular disease.Recent FindingsTo date, accumulated evidence regarding oxidation as a pro-atherogenic factor indicates that redox biochemical events involved in atherogenesis are indeed a very attractive target for the management of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 124 publications
0
23
0
1
Order By: Relevance
“…Overproduction of oxLDL triggers the LOX-1 expression in VSMCs and also triggers apoptosis ( Wu et al, 2017 ). Expression of the proapoptotic protein Bcl-2-associated X protein (Bax) is increased, as well as the expression of the anti-apoptotic protein Bcl2 in response to excessive oxLDL formation ( Liu et al, 2005 ; Toledo-Ibelles and Mas-Oliva, 2018 ). LOX-1 mediates this effect, and, accordingly, anti-LOX-1 antibodies inhibit the ox-LDL-induced apoptosis.…”
Section: Oxidative Modification Hypothesismentioning
confidence: 99%
“…Overproduction of oxLDL triggers the LOX-1 expression in VSMCs and also triggers apoptosis ( Wu et al, 2017 ). Expression of the proapoptotic protein Bcl-2-associated X protein (Bax) is increased, as well as the expression of the anti-apoptotic protein Bcl2 in response to excessive oxLDL formation ( Liu et al, 2005 ; Toledo-Ibelles and Mas-Oliva, 2018 ). LOX-1 mediates this effect, and, accordingly, anti-LOX-1 antibodies inhibit the ox-LDL-induced apoptosis.…”
Section: Oxidative Modification Hypothesismentioning
confidence: 99%
“…Antioxidant therapy such as febuxostat, an inhibitor of xanthine oxidase, also functions partly through effects on macrophages [140]. Antioxidant therapy could modify the process of atherogenesis by preventing oxidation of LDL, formation of ROS, and subsequent release of inflammatory cytokines in macrophages [141]. Clinical trials targeting other molecules, including CX3CR1, IL-12, LXR, IRF5, and PPAR- γ , are still on the way and have not reached any conclusion.…”
Section: Therapeutic Strategies Targeting Macrophage-dependent Infmentioning
confidence: 99%
“…Several herbal formulations have been reported in the literature for the treatment of hypercholesterolemia and diabetes that were used historically by local populations of people based on traditional knowledge passed down from generation to generation [4][5][6][7]. Dietary supplements of antioxidant formulations are also available to ameliorate risk factors associated with hypercholesterolemia [8][9][10]. Several studies have indicated that the use of plant-derived antioxidant formulations are more preferred than synthetic drugs to reduce oxidative injury [11].…”
Section: Introductionmentioning
confidence: 99%